Issues and Challenges of Non-Bank Financial Institutions in Bangladesh - Hassan, Md. Rizwan (Asian Business Review, 2013)
The article examines the issues and challenges faced by non-bank financial institutions in Bangladesh. At present the main concern of NBFIs of Bangladesh is collecting fund for investment at a lower cost. Due to current liquidity crisis of banks, it became difficult for them to have funds at a reasonable cost. Other issues stem from severe competition from banks, volatile stock market, and lack of trained human resource and absence of secondary market for loan products. It is suggested that NBFIs have to search for alternative and low cost source of funds, find appropriate way to diversify their product in a manner attractive to people and restrict their investment in low-risk project.